Expression of mRNA encoding the macrophage colony-stimulating factor receptor (c-fms) is controlled by a constitutive promoter and tissue-specific transcription elongation. - Yue, X (1993)
The gene encoding the receptor for macrophage colony-stimulating factor 1 (CSF-1), the c-fms protooncogene, is selectively expressed in immature and mature mononuclear phagocytes and trophoblasts. Exon 1 is expressed only in trophoblasts. Isolation and sequencing of genomic DNA flanking exon 2 of the murine c-fms gene revealed a TATA-less promoter with significant homology to human c-fms. Reverse transcriptase primer extension analysis using exon 2 primers identified multiple clustered transcription initiation sites. Their position was confirmed by RNase protection. The same primer extension products were detected in equal abundance from macrophage or nonmacrophage sources of RNA. c-fms mRNA is acutely down-regulated in primary macrophages by CSF-1, bacterial lipopolysaccharide (LPS), and phorbol myristate acetate (PMA). Each of these agents reduced the abundance of c-fms RNA detectable by primer extension using an exon 3 primer without altering the abundance of presumptive short c-fms transcripts detected with exon 2 primers. Primer extension analysis with an intron 2 primer detected products at greater abundance in nonmacrophages. Templates detected with the intronic primer were induced in macrophages by LPS, PMA, and CSF-1, suggesting that each of the agents caused a shift from full-length c-fms mRNA production to production of unspliced, truncated transcripts. The c-fms promoter functioned constitutively in the RAW264 macrophage cell line, the B-cell line MOPC.31C, and several nonhematopoietic cell lines. Macrophage-specific expression and responsiveness to selective repression by LPS and PMA was achieved by the incorporation of intron 2 into the c-fms promoter-reporter construct. The results suggest that expression of the c-fms gene in macrophages is controlled by sequences in intron 2 that act by regulating transcription elongation.